RETRACTED: Consumer Behavior and COVID-19: Comparing Purchase Incentives and Ecological Awareness Changes - Letunovska Nataliia; Ziabina Yevheniia; Lyulyov Oleksii; Pimonenko Tetyana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 456, 00002 (2023), https://doi.org/10.1051/e3sconf/202345600002